The "Doula" in accompanying the end-of-life - Alfano, Linda; Malcotti, Ivano; Ciliberti, Rosagemma (Medicina Historica, 2023)
Since time immemorial, the occurrence of death and adjoined burial ceremonies have been at the core of critical anthropological challenges that have depicted and proved the social-cultural value of this topic moment throughout the ages.Recently, several social factors, along with the development of biomedical techniques and the increasing medicalization of man in his life course, have changed the appearance of death.In the industrialized and urbanized areas of contemporary society, death has progressively shed the 'naturalness' of a difficult moment that always has concerned the inner circle of family, to further has been frequently relegated to medical or, at least medicalized, context in which the demise takes place long gone from the gazes and affections of kin and beloved ones. Against a context in which the medical technique becomes increasingly intrusive, the innermost anguish of the dying individual is consumed: that of being abandoned to a solitary confrontation with life's most tormented event, at a time when according to medical science "there is nothing left to act”.Therefore, these contingencies oblige contemporary bio-medical ethics to rethink the moral and accompanying rules at the end of life that validly regulated this arena in the past, but which at present appear outdated and insufficient. To this end, the authors analyze the figure of the "End-of-Life Doula", a figure who can intercept the social need revolving around the subject of death, by offering the dying person and family members support, comfort, and a meaningful response to the ordeal of death.